From sculpture in ancient Greece to trade symbols in the architecture of Odesa (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The relevance of the topic is due to the need to study and reveal the historical objects of architecture of Greece and southern Ukraine, in particular the city of Odesa, which influenced the formation of a unique image of buildings and structures. Analysis of different styles in architecture can be useful in restoration works on the reconstruction of architectural monuments. The Greeks always believed that only in a beautiful body can live a beautiful soul. Therefore, the harmony of the body, external perfection is an indispensable condition and the basis of an ideal person. The Greek ideal is defined by the term kalokagatia (Greek: kalos - beautiful, agathos - good). Since kalokagathia includes the perfection of both bodily and spiritual and ethical makeup, the ideal carries justice, chastity, courage and intelligence along with beauty and strength.Along the shores of the Black Sea, on the coast of Southern Italy, there was a group of slave states known in history as Ancient Greece, or Hellas. In the XII-VII centuries BC in Ancient Greece there was a decomposition of the primitive communal system and patriarchal slavery appeared, which in the VIII-VI centuries BC formed the basis of the economic and political life of society. The commodity-money economy developed, which was concentrated in slave cities-states (polis). The largest among them were Athens and Sparta, whose struggle for dominance in ancient Greece was simultaneously a struggle between democracy and aristocratic oligarchy, which led to the Peloponnesian War of 431-404 BC. The Greek polis, exhausted by the war, fell under the rule of Macedonia in 338 BC.For the purpose of comparative analysis, the study includes buildings of the early period, which arose in Odesa from 1880 to 1910. The range of the studied buildings includes public buildings: commercial, entertainment and administrative, which were built in that period.Each building of the central part of the city is unique in the range of elements and details used, in the compositional solution, in the unique decoration of facades and interiors. It is necessary to identify the characteristic features that were developed in the architecture of the city of different periods: modern, constructivism, minimalism. Identification of stylistic trends and directions makes it possible to avoid mistakes in the process of reproducing the executed elements and details on the example of trade symbols.
Keywords: ancient sculpture; architecture; ancient Greece; trade symbols